(untitled) (International Seven Journal of Multidisciplinary, 2023)
The paper discusses the importance of the teaching knowledge needed to work with Youth and Adult Education. We used the theories of Beiseigel (1974), Freitas (2009), Souza (2007) and Freire (2006) as reference sources, contextualizing the first manifestations for the creation of YAE. Gauthier (2006), Pimenta (2005) and others talk about the knowledge that is necessary for a better educational development of students in Youth and Adult Education and Caldart (2002), Hage (2014) who discusses Rural Education. After these considerations, we will present an analysis of the answers obtained from an interview, relating them to the authors’ ideas.